2015
DOI: 10.1167/iovs.14-15349
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Feasibility Studies of Intraocular Use of Polyethylene Glycol–Based Synthetic Sealant to Close Retinal Breaks in Porcine and Rabbit Eyes

Abstract: Polyethylene glycol-based synthetic sealant appeared to effectively seal retinal breaks and was not toxic to the eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Upon exposure to xenon light (450-500 nm) for 40-60 s, the prepolymer solution formed a solid, crosslinked hydrogel. The adhesive remained attached for 24 h despite a forceful squirt of balanced salt solution, showed little inflammatory reaction in the eyes during 28 days of follow up, and the electroretinography also did not show any abnormality or inflammation [81]. In addition, the authors also conducted an in vivo study to investigate the application of this photo-curable PEG-based sealant for the closure of sutureless sclerotomies (surgical incision of the sclera) in microincisional vitrectomy surgery (MIVS) using a Dutch pigmented rabbit eye model (Fig.…”
Section: Peg-based Adhesivesmentioning
confidence: 91%
See 1 more Smart Citation
“…Upon exposure to xenon light (450-500 nm) for 40-60 s, the prepolymer solution formed a solid, crosslinked hydrogel. The adhesive remained attached for 24 h despite a forceful squirt of balanced salt solution, showed little inflammatory reaction in the eyes during 28 days of follow up, and the electroretinography also did not show any abnormality or inflammation [81]. In addition, the authors also conducted an in vivo study to investigate the application of this photo-curable PEG-based sealant for the closure of sutureless sclerotomies (surgical incision of the sclera) in microincisional vitrectomy surgery (MIVS) using a Dutch pigmented rabbit eye model (Fig.…”
Section: Peg-based Adhesivesmentioning
confidence: 91%
“…(Scale bar: 500 μm). Adapted from Hoshi et al[81] with permission from Association for Research in Vision and Ophthalmology, copyright 2016.…”
mentioning
confidence: 99%
“…Hoshi et al demonstrated that FocalSeal PEG (Genzyme Corporation) successfully sealed in vitro porcine retinal tears 11. Hoshi et al also used PEG to seal sclerotomies post vitrectomy surgery in rabbit eyes 85.…”
Section: Retina Surgerymentioning
confidence: 99%
“…FocalSeal was used with 100% success as a supplement to sutures or staples to repair air leaks after pulmonary resection in pigs [77]. It was also used successfully to repair retinal breaks [78].…”
Section: Synthetic Hydrogel Sealants 2251 Photocrosslinkable Polymentioning
confidence: 99%